2013
DOI: 10.3747/co.20.1066
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survivorship and South Asian Women: Understanding about the Follow-Up Care Plan and Perspectives and Preferences for Information Post Treatment

Abstract: be experienced in common with bcss of other ethnic backgrounds, but the present study also suggests the presence of unique cultural nuances such as spiritual and language-specific support resource needs. The results provide direction for designing key content and format of scps, and information about elements of care that can be customized to individual patient needs. KEY WORDSSouth Asian women, breast cancer survivors, survivorship care, social and cultural aspects of cancer, psychosocial and physical functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(103 citation statements)
references
References 42 publications
3
100
0
Order By: Relevance
“…Survivors preferred to have specific areas of concern addressed on a SCP, such as information on signs and symptoms of recurrent cancer, fatigue, cognitive changes, depression, anxiety, spiritual guidance, and relationship changes [22,41,42,48,49,51]. Survivors also requested improved communication of information on healthy living recommendations, such as nutrition and exercise, late and long-term effects, a record of care/treatment summary, and which provider is responsible for follow-up testing and care [37,49,51].…”
Section: Cancer Survivor Scp Preferencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Survivors preferred to have specific areas of concern addressed on a SCP, such as information on signs and symptoms of recurrent cancer, fatigue, cognitive changes, depression, anxiety, spiritual guidance, and relationship changes [22,41,42,48,49,51]. Survivors also requested improved communication of information on healthy living recommendations, such as nutrition and exercise, late and long-term effects, a record of care/treatment summary, and which provider is responsible for follow-up testing and care [37,49,51].…”
Section: Cancer Survivor Scp Preferencesmentioning
confidence: 97%
“…Almost half of the papers included perspectives of health care providers; six included oncology providers (i.e., oncologists, nurses, and nurse practitioners), four included PCPs, and four included both. Three papers exclusively included perspectives of cancer survivors who self-identified to be minority: two with South Asian women and one with African American women [37,47,48]. Sixty percent of the studies were conducted in the USA (n= 18), with the remainder in Canada (n=7), Australia (n=3), and the UK (n=1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A recent evaluation of the care plans of 36 breast cancer survivors and 21 head-and-neck cancer survivors in Alberta, including interviews with the physicians, nurses, and patients involved, suggested that care plans can enhance communication between survivors and care providers and that survivors appreciate individualized attention and comprehensiveness in a care plan 27 . The importance of providing cancer survivors with individualized information has been reported elsewhere 28,29 . The data gained from the present study could be used in part to inform the development survivorship care plans for several of the major types of cancer, including breast, prostate, gynecologic, and cutaneous malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies with sa and other migrant women from diverse backgrounds and countries of origin have reported that the experience of a cancer illness might be coloured by difficulties related to the immigration experience and living in an altered culture 17,25,27,40 . Such challenges include a wide range of stressors, such as financial burdens, uprooting and resettlement experiences, difficulties in providing adequate health care for members of the extended family, the struggle to keep their beliefs and values related to the upbringing of children, and maintaining activities of daily living 25 .…”
Section: Discussionmentioning
confidence: 99%